Preface / Ts Jamal Othman - Othman, Jamal (Unit Penerbitan JSKM, 2021)
First and foremost, I would like to express my gratitude to the editorial team for their enthusiasm and diligent in making this edition published punctually. On behalf of the editorial board, I wish to express my sincere appreciation to our coordinator, Mrs. Norazah Umar, which give the moral supports in the completion of this edition. Thanks to all authors for your participation and without your support, this publication is impossible. The first edition has been published in 2020 with 18 papers contributed by the authors. The authors had shared ideas, tips, creativities, innovations and new experiences among educators applies attractive tools, applications, systems and peripherals to conduct the online class to their students effectively. Through this sharing, the readers will gain knowledge and experience on how to improve the teaching and learning curve among students and educators. Indirectly it helps the community to develop their knowledge and skills that they will need in a digital age: not so much digital skills, but the thinking and knowledge that will bring them success in future obstacles and challenges.